The association between the fluoxetine use and the occurrence of coronary heart disease: a nationwide retrospective cohort study - Fang-Ling Li; Yu-Tse Sheih; Ming-Hsun Lin; Yong-Chen Chen; Wen-Tung Wu; Tsung-Kun Lin; Yu‐Ching Chou; Chien‐An Sun (BMC Cardiovascular Disorders)
Abstract Background We explored if the administration of fluoxetine, recognized for its potential in adipocyte browning, entails a differential risk of coronary heart disease (CHD) in comparison to other SSRI medications. Methods Using the National Health Insurance Research Database of Taiwan from 2000 to 2013, we conducted a retrospective cohort study. The exposure cohort comprised individuals prescribed fluoxetine for over 90 days (n = 2,228). Conversely, those administered other SSRIs (excluding fluoxetine) for a duration surpassing 90 days were designated as the non-exposed cohort (n = 8,912). CHD incidence served as our primary outcome measure, and we employed Cox proportional hazards models to scrutinize the relationship between fluoxetine exposure and CHD development rates. Results Compared with the non-exposed cohort, the fluoxetine use had a significantly decreased 21% risk of developing CHD in the exposed cohort (adjusted hazard ratio: 0.79%, 95% confidence interval: 0.68–0.92). Noticeably, results indicated that there was an inverse association between the fluoxetine exposure and the risk of CHD, regardless of whether men, women or other age groups. Conclusion Our findings suggest that clinical use of fluoxetine was associated with a 21% reduced risk of CHD relative to other SSRI prescriptions.